Study of Post-Conflict Disintegration of The Malayu-Madura Ethnic In Sambas, West Kalimantan - Emita, Emita; Dewantara, Jagad Aditya; Zakso, Amrazi (Universitas Tanjungpura, 2024)
The research describes the aftermath of the Malayu-Madura ethnic conflict which refers to disintegration in Sambas, West Kalimantan. Through this research, it is hoped to find out what happened after the Malay ethnic conflict today. The method used in the research uses a qualitative approach with a case study research design. The data sources in this research focus on post-Malayu-Madura ethnic conflict phenomena. The data collection techniques used were observation, interviews and documentation. Data analysis techniques use data reduction analysis, data presentation, and drawing conclusions. The results of this research found social changes caused by the conflict between the Malayu ethnic group and the Madura ethnic group, as evidenced by the social shift between the Malayu ethnic group and the Madura ethnic group, which initially had good integration, but with the conflict, changes occurred which referred to disintegration. The occurrence of societal changes in the form of increasingly complex social differentiation, as a result of the conflict between the Malayu ethnic group and the Madura ethnic group, has had a major impact so that the Malayu and Madura ethnic groups have not been able to live side by side in Sambas, West Kalimantan. The causal factor that refers to disintegration is due to an agreement by the previous older generation that they would not accept the Madura ethnic group back, then this was continued by the generation below. This is supported by the existence of trauma from the older generation, but the generation below does not have any trauma.